Treatment of high strength wastewater by thermophilic aerobic membrane reactor and possible valorisation of nutrients and organic carbon in its residues. (20th January 2021) - Collivignarelli, Maria Cristina; Abbà, Alessandro; Bertanza, Giorgio; Baldi, Marco; Setti, Massimo; Frattarola, Andrea; Carnevale Miino, Marco
Abstract: The depletion of nitrogen and phosphorus represents a significant problem. Two real high strength wastewaters were treated by Thermophilic Aerobic Membrane Reactor (TAMR), an advanced biological process, obtaining significant removal of pollutants. Unlike the previous works, this paper does not focus on the optimization of the performance of the TAMR, but it studied the possible reuses of liquid (permeate) and solid (biological excess sludge) matrices to recover organic carbon, nitrogen and phosphorus and promote a circular economy model. The high nitrogen content of permeate can be exploited stripping ammonia with performances higher than 80% in best conditions to produce ammonium sulphate (useful as fertilizer). Moreover, the respiromeric tests demonstrated that permeate can be used in conventional active sludge systems as external source of organic carbon granting similar denitrification rate as methanol. In the sludge residue extracted from TAMR a significant presence of organic carbon and phosphorus (as hydroxyapatite) were revealed demonstrating the feasibility of recover this residue in land application. A preliminary management costs estimation showed that TAMR, coupled with a stripping and adsorption system to recover nutrients, is economically sustainable. Graphical abstract: Image 1 Highlights: Chemical oxygen demand (42–78%) and phosphorus (70–79%) were removed. More than 80% of ammonia in permeate can be stripped to produce ammonium sulphate. Permeate and methanol allow similar denitrification rate. Hydroxyapatite was detected in sludge of thermophilic aerobic membrane reactor. Preliminary management costs analysis highlights the economic feasibility.